Beautoklavio putbetonio šiluminių techninių savybių tyrimai - Gnip, Ivan; Keršulis, Vladislovas; Laukaitis, Antanas (Journal of Civil Engineering and Management, 1996)
Investigation into non-autoclaved foam concrete heat engineering propertiesThe purpose of this investigation was to determine various density foam concrete heat engineering properties. These properties are not included in valid construction standards [1].Thermal conductivity of samples was determined at 25°C according to [2], specific heat – [3], vapour permeability –[4] and sorption moisture – [5].Dry foam concrete thermal conductivity (W/m-K) dependency on its density is given in Fig. 1 as well as after mathematical statistical treatment using the regressive equation [1].Foam concrete thermal conductivity dependency on its humidity statistical analysis results is given in Table 1, here ΔλW s and ΔλW t is the average absolute thermal conductivity increase for 1% materials moisture according to mass and volume, while and δW s δW t is the same increase, but in percentage value. Foam concrete thermal conductivity dependency on moisture is linear.The specific heat value for 245 and 840 kg/m3 density foam concrete is 980±50 and 850±50 J/kg·K respectively.The determined foam concrete sorption moisture is given in Fig. 2 and Table 2. The steep moisture increase at high ambient air humidity is defined by adsorption and the beginning of capillary condensation. This state is not noted in literature curve 2 [7] and evidently due to the short experimental interval.The vapour permeability results for foam concrete are given in Fig. 3 and using the regressive equation (2). Our results are approximately 13% lower than those given for porous concrete [1].The calculated thermal conductivity was determined using equation (3), assuming that the sorbtion moisture is equal to the relative air humidity (80–85)% (Table 2). Then 250, 500 and 800 kg/m3 density foam concrete λ(ρ0, Wsk) is equal to 0,12, 0,19 and 0,32 W/m·K respectively.The foam concrete heat capacity coefficients S, calculated according to formula (4) for temperature fluctuation period z=24 h and according to damp foam concrete density and specific heat are given in Table 3.Experimental for 260, 500 and 800 kg/m3 density non-autoclaved foam concrete heat engineering values are given in Table 4. For comparison, the denominators (under the line) show the corresponding values for porous concrete given in [1], It is purposive to use in practical calculation specific non-autoclaved foam concrete heat engineering values because these differences are substantial.Article in Lithuanian.First Published Online: 26 Jul 2012